2021
DOI: 10.3390/f12101402
|View full text |Cite
|
Sign up to set email alerts
|

Recreation and Therapy in Urban Forests—The Potential Use of Sensory Garden Solutions

Abstract: Urban forests are not only woodlands or groups of trees, but also individual trees, street trees, trees in parks, trees in derelict corners, and gardens. All of which are located in urban and peri-urban areas and diversify the landscape and provide a wide range of social benefits. Sensory gardens play a specific therapeutic and preventive role. Designing such gardens as a recreational infrastructure element can successfully enrich urban forests. Following the principles of universal design may provide enjoymen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 47 publications
(43 reference statements)
0
10
0
Order By: Relevance
“…Survey research (n = 15, 5.6%) included both large-scale general population surveys [54] and targeted onsite intercept surveys of forest visitors engaged or interested in forest therapy experiences [55,56]. Research types used in less than 10 articles included expert assessments such as suitability analyses [57,58] and site inventories [59], image analysis of virtual landscape representations [60] and social media selfie posts [61], and epidemiological studies [62].…”
Section: Study Sample Characteristicsmentioning
confidence: 99%
“…Survey research (n = 15, 5.6%) included both large-scale general population surveys [54] and targeted onsite intercept surveys of forest visitors engaged or interested in forest therapy experiences [55,56]. Research types used in less than 10 articles included expert assessments such as suitability analyses [57,58] and site inventories [59], image analysis of virtual landscape representations [60] and social media selfie posts [61], and epidemiological studies [62].…”
Section: Study Sample Characteristicsmentioning
confidence: 99%
“…Wajchman et al, [23] carried out an experiment in Poland; in this study they examined 15 gardens and a sensory path. From this study they concluded that gardens have therapeutic function that is based on the effect of plants on both the physical and mental well-being and the treatment might be passive or strong.…”
Section: Importance Of Sensory Gardenmentioning
confidence: 99%
“…Conservation strategies and successes reported in past studies highlight the importance of values attached to the subject to be protected (Arnberger & Eder, 2015;Cai et al, 2021;Endreny et al, 2017;Lamhamedi et al, 2021;Levandovska et al, 2020;Massawe et al, 2021;Wajchman-Świtalska et al, 2021) meaning, people protect what they value. The rank for conservation measures and efforts in this study can be attributed to the recognition of the benefits of urban forests outlined in the first theme above.…”
Section: Conservation Measuresmentioning
confidence: 99%